A novel lightweight key management scheme for RFID-sensor integrated hierarchical MANET based on internet of things. (2017) - Kumar, Adarsh; Gopal, Krishna; Aggarwal, Alok
A mobile ad-hoc network (MANET) is a group of low power computing mobile and wireless devices which cooperatively form an infrastructure-less and decentralised network. Scarcity of resources in MANET devices requires secure, efficient and lightweight mechanisms for network construction, its management and administration. Teo and Tan (2005) proposed efficient key management approach for hierarchical MANET. In this work, Teo and Tan's circular hierarchical model is extended for dynamic group construction. In proposed mechanism lightweight primitives and protocols are integrated for security and results show that it provides strong authentication, confidentiality, forward and backward secrecies. The comparative analysis shows that the proposed mechanism is having lesser cost in terms of number of messages exchange and there is an improvement of 6.6% for gate equivalents (GEs) as compared to Teo and Tan's protocol. Further, the proposed mechanism provides higher throughput and minimum delay compared to Teo and Tan's protocol.